Management options for proximal humerus fractures – A systematic review & network meta-analysis of randomized control trials. Issue 2 (February 2022) - Davey, Martin S.; Hurley, Eoghan T.; Anil, Utkarsh; Condren, Saorise; Kearney, Jack; O'Tuile, Cathal; Gaafar, Mohammed; Mullett, Hannan; Pauzenberger, Leo
Highlights: This study performed a network meta-analysis of 13 randomized control trials including 836 patients in evaluation of optimal treatment options of displaced proximal humerus fractures. The results of this study demonstrate that Reverse Shoulder Arthroplasty offers patients satisfactory clinical outcomes, including the greatest range of motion with comparable patient-reported outcomes post-operatively when contrasted to other management modalities. Although conservative management had the lowest rate of subsequent surgeries, Reverse Shoulder Arthroplasty had the lowest rates of post-operative complications and surgical revisions. Abstract: Aims: The purpose of this study is to systematically review the randomized controlled trials on the various treatment options that can be utilized in the management of displaced proximal humerus fractures. Materials & Methods: Based on the PRISMA guidelines, three independent reviewers performed a systematic review of the literature. Randomized control trials (RCTs) focusing on the outcomes of the following interventions in the management of PHFs were considered for inclusion; (1) non-operative or conservative (NOC) management, (2) open reduction and internal fixation (ORIF), (3) intra-medullary nailing (IMN), (4) shoulder hemi-arthroplasty (HA), and (5) reverse shoulder arthroplasty (RSA). Network meta-analyses were performed using R and studies were ranked according to their P-score. Results: Our study included 13 RCTs. RSA had improvements in abduction, constant score, flexion, as well as lowest rates of malunion and osteonecrosis when compared to other management modalities (P-Score = 0.9786, P-Score = 0.9998, P-Score = 0.9909, P-Score = 0.9590 and P-Score = 0.8042 respectively). HA was found to have improvements in health-related quality of life scores when compared to other management modalities (P-Score = 0.9672). ORIF had the highest improvement in quick disability of arm, shoulder and hand scores and visual analogue scale scores (P-Score = 0.8209 and P-Score = 0.7155 respectively). NOC was found to have the lowest rate of conversion to surgical intervention, with RSA having the lowest rate of surgical interventions (P-Score = 0.9186 and P-Score = 0.7497 respectively). Discussion & Conclusion: RSA offers satisfactory improvements in clinical and functional outcomes when compared to other non-operative and operative treatment options in the management of carefully selected proximal humerus fractures, with a minimal revision rate when compared to other surgical management modalities. Level of Evidence: I - Systematic Review & Meta-Analysis of Randomized Control Trials